Research into a possibility to prolong the time of operation of universal open top wagon bodies that have exhausted their standard resource - Okorokov, Andrii; Fomin, Oleksij; Lovska, Alyona; Vernigora, Roman; Zhuravel, Irina; Fomin, Volodimir (Eastern-European Journal of Enterprise Technologies, 2018)
The intensification of utilization of railroad cars predetermines the wear of their bodies as the most loaded element of design and necessitates the introduction of new cars. To reduce the cost of manufacturing new car designs, it is proposed to prolong the operation of universal open top wagon bodies beyond standard 1.5 operation terms. When carrying out calculations for strength under conditions of wagon building enterprises, the normative magnitudes of loading are applied, which do not take into consideration possible wear in the elements of bearing structures of open top wagon bodies under operation. This can lead to a significant error when determining a possibility to extend a period of operation of open top wagon bodies that have exhausted their standard resource. Therefore, when substantiating a possible prolongation of the operation period of cars it is important to take into consideration, at the stage of strength estimations, the refined magnitudes of dynamic loads acting on them in operation. To investigate dynamic loading acting on a open top wagon body during an impact at shunting, which is the case of the greatest loading to its structure, we employed mathematical modeling. The results of present research allowed us to conclude that the acceleration that acts on the bearing structure of a open top wagon with the wear characteristic of 1.5 terms of operation during an impact at shunting is about 4g. In addition, research into dynamic loading of the bearing structure of a open top wagon body during an impact at shunting was performed using computer simulation based on the software CosmosWorks. The research results showed that the maximum accelerations of a open top wagon body make up approximately 5g. To verify the adequacy of the developed models, we used the Fisher criterion. Results of the calculations have shown that the hypothesis of adequacy is not contradicted. The research results obtained were taken into consideration when determining strength indicators of a open top wagon body with the wear characteristic of 1.5 terms of operation. To this end, we constructed a spatial computer model of the body of a base open top wagon, model 12-757, whose bearing elements are of the thickness corresponding to the minimally defined one. The calculation employed a method of finite elements. Based on the performed calculations it was determined that the maximum equivalent stresses do not exceed the permissible ones and make up about 345 MPa, which makes it possible to draw a conclusion about the possibility of further utilization of a railroad car. The study conducted would help determine the feasibility of prolongation of service operation of open top wagons that have exhausted their standard resource.